A comprehensive review on the application of active packaging technologies to muscle foods. (December 2017) - Ahmed, Ishfaq; Lin, Hong; Zou, Long; Brody, Aaron L.; Li, Zhenxing; Qazi, Ihsan M.; Pavase, Tushar R.; Lv, Liangtao
Abstract: Since the beginning of the current millennium, innovations in food packaging systems have evolved as response to the continuous changes in market trends and consumer's preferences for convenient, safe, healthy and quality food products. Active packaging (AP) system provides such functionalities to facilitate these demands and offers role beyond the traditional protection and inert barrier to the external environment. Various AP components such as antimicrobials, antioxidants, O2 scavengers, CO2 emitters/absorbers, moisture regulators, flavor releasers, and absorbers have been deliberately included in the package system for augmenting packaging performance. These constituents delay or stop chemical, microbial, enzymatic and oxidative spoilage, control weight loss, retain color and integrity of meat based products. Currently, the use of edible or biodegradable materials, plant extracts and nanomaterials are expected to substitute synthetic additives due to their packaging and waste management notions. This article reviews the principles and technological advances as well as the global patents and future research trends in AP sector with their applications focused on meat products. Highlights: Use of AP technologies minimize hazards and enhance the quality and safety of muscle foods from farm to fork. Technological breakthroughs in AP sector lead to microbial growth inhibition, delayed oxidation and moisture regulation. The use plant extracts and nano-particles in AP seem very promising. Industrial recognitions and consumer acceptance about the efficacy of this system are crucial for commercial realizations.